Petrogenesis of silica-saturated and silica-undersaturated syenites in the northern North China Craton related to post-collisional and intraplate extension - Yang, J.; Sun, J.; Zhang, M.; Wu, F.; Wilde, Simon (Elsevier Science BV, 2012)
Whole-rock major and trace element and Sr-, Nd- and Hf-isotope data, together with zircon U–Pb and Hf-isotope data, are reported for three alkaline intrusions (Liangjia, Jianfang and Hekanzi) in the Yanshan Fold and Thrust Belt in the northeastern North China Craton, in order to investigate their sources, petrogenesis and tectonic implications. The Liangjia and Jianfang plutons are mainly composed of medium-grained quartz syenites, whereas, the Hekanzi complex consists of nepheline-bearing pyroxene-biotite syenites. Zircon U–Pb dating gives emplacement ages of 254–246 Ma for the Liangjia and Jianfang silica-saturated syenites and 226–224 Ma for the Hekanzi silica-undersaturated syenites. The Late Permian silica-saturated alkaline rocks have high silica contents (SiO2 = 69.2–75.7 wt.%) and low MgO (0.04–0.47 wt.%) concentrations, and are enriched in large ion lithophile elements (LILEs) and light rare earth elements (LREEs) but with negative Eu, Ba and Sr anomalies and depletion in high field strength elements (HFSEs), with significant negative Nb, Ta, P and Ti anomalies.Geochemical data and Sr-, Nd and Hf-isotopic compositions indicate that they were mainly derived from partial melting of lower crustal materials with extensive pyroxene and plagioclase fractionation. The Triassic silica-undersaturated syenites have relatively high MgO abundances (up to 5.3 wt.%) at basic to intermediate silica contents. They are enriched in LREE and LILE and depleted in HREE and HFSE, with negative Nb, Ta and Ti anomalies. They have relatively low initial 87Sr/86Sr ratios and relatively negative whole rock εNd(t) and εHf(t) values and zircon εHf(t) values. All these geochemical features indicate that they were the result of crustal assimilation and fractional crystallization of a mafic magma derived from an amphibole-clinopyroxene-rich lithospheric mantle via small degree partial melting. Based on the regional geology, the Late Permian syenites would form in a post-collisional extension setting, whereas, the Triassic syenites were most likely generated in an intraplate extensional setting, providing time constraints on the geodynamic transition from post-orogenic to intra-plate extension.